A bioinspired multi-agent system based on monocular vision. (2017) - Falleiros, Evandro Luís Souza; Ishii, Renato Profirio; Calvo, Rodrigo
Develop multi-robot real-time applications is a complex task. In order to deal with such scenarios, this paper proposes PheroSLAM, a bio-inspired multi-robot system based on monocular camera, which adopt an extended version of ant colony optimisation approach to coordinate multiple-robot teams. Moreover, robots launch repulsive artificial pheromone around themself, creating a repulsive trail in PheroSLAM system. A vision-based mechanism is also used to provide visual odometry and to build a 3D feature-based map, considering that every robot must be able to localise itself in the explored environment. Therefore, the relevance of the proposal is to extend an SLAM problem for many robots and promote the robots move autonomously in the environment according a bio-inspired coordination strategy. Experimental evidences indicated the dispersibility of the PheroSLAM system, increasing the covered area of an environment. Also, results showed that the coordination strategy is efficient and satisfactory to accomplish the exploration task.